농식품 이력추적관리제도의 운영 평가 분석 - 이계임 (한국농촌경제연구원, 2012)
This study aims to analyse traceability in terms of laws, management systems and consumer recognition. The laws concerning traceability systems were scattered around by the category of food and the purpose of managing respective systems was not clearly defined while showing significant differences in terminologies, items to be recorded, method of labelling and provisions for punishments as well. As the systems are operated with the structure of multiple systems by category of food, the problems such as unnecessary division of similar works and the possibility to make consumers confused are incurred. And also the problems such as different emphasis steps by system and absence of linkage between systems are appeared as well. The result of a questionnaire survey on consumers revealed that consumers who considered the existence of traceability system at the time of purchase of food were very little, and the consumers who responded that they knew the term ‘traceability system’ were not more than 6.6%.
Keywords: 이력추적관리제도; 법률평가; 운영방식; 소비자 조사; traceability system; legal evaluation; operation system; consumer survey